Digital twin concept: Healthcare, education, research - Maria Peshkova; Valentina Yumasheva; Ekaterina Rudenko; Natalia Kretova; Peter Timashev; Tatiana Demura (Elsevier, 2023)
Introducing the concept of digital twins in healthcare, medical education, and research is a complex multistage challenge requiring participation of multidisciplinary teams. In pursuing this goal, we have created a validated database of scans of colorectal tumor slides associated with relevant clinical and histological information. This database is also linked to the blood bank, which opens a wide range of opportunities for further research. Herein, we present our experience within the scope of the digital twins initiative.